SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KOMPUTER BERDASARKAN KOMPONEN MENGGUNAKAN METODE HYBRID AHP DAN MOORA BERBASIS WEB - Febian Ageng Resta; Siti Aminah (STMIK Dian Cipta Cendikia Kotabumi, 2022)
Technological advances are developing so fast in today's era, and this influence is unavoidable. Especially the digitization of various fields to make it easier for users to make work shorter and faster, as well as make work more efficient. The variety of choices of computer components is one of the obstacles in assembling a desktop computer because not all component choices can work properly according to what the user wants. This study aims to overcome this problem by implementing a component-based computer selection decision support system using the hybrid AHP and MOORA methods in order to obtain the best recommendation results in the selection of desktop computer components which are then packaged in a web page. The application of the hybrid AHP and MOORA methods is expected to produce accurate information regarding the selection of computers based on components. The results obtained from this study are the formation of a component-based computer selection decision support system model using the web-based AHP and MOORA hybrid methods.